(3GdYHGH aj TQM CHjGJ GdBOGHs - (3TQa GdOjf MSf Hf Ydj Hf UGdM GdaOhis; (3LYaQ Hf TeS GdNdGaIs
(3ChdgG (B:s
(3GdMeO ddg GdcHjQ GdeJYGd GdPi de jRd hdG jRGd , GdefaQO SHMGfg HGdceGd s
(3BNQgG (B:s
(3BNQg bhd GdeJfHi aQH cFjH djS JfOi Lahfg hQH cKjQ GdOeY ZjQ cFjH s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG HYV GdJYdjbGJs
(3HYV GdChQGb HNW eZGjQ JQJjH GdChQGb eVWQH ai HYV GdCeGcfs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs